2002
DOI: 10.1021/es0113854
|View full text |Cite
|
Sign up to set email alerts
|

Probability of Nitrate Contamination of Recently Recharged Groundwaters in the Conterminous United States

Abstract: A new logistic regression (LR) model was used to predict the probability of nitrate contamination exceeding 4 mg/L in predominantly shallow, recently recharged groundwaters of the United States. The new model contains variables representing (1) N fertilizer loading (p < 0.001), (2) percent cropland-pasture (p < 0.001), (3) natural log of human population density (p < 0.001), (4) percent welldrained soils (p < 0.001), (5) depth to the seasonally high water table (p < 0.001), and (6) presence or absence of uncon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
206
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(225 citation statements)
references
References 27 publications
15
206
0
4
Order By: Relevance
“…For example, 9% of U.S. domestic wells sampled during 1993-2000 had nitrate concentrations exceeding the U.S. Environmental Protection Agency's (EPA) maximum contaminant level of 10 mg⅐liter Ϫ1 as N (8). In the Yakima River Basin of Washington State, where this study was conducted, 13% of the samples taken from small-watershed sites exceeded the EPA's maximum contaminant level, indicating a potential health risk to nearby residents with shallow wells (9).…”
mentioning
confidence: 99%
“…For example, 9% of U.S. domestic wells sampled during 1993-2000 had nitrate concentrations exceeding the U.S. Environmental Protection Agency's (EPA) maximum contaminant level of 10 mg⅐liter Ϫ1 as N (8). In the Yakima River Basin of Washington State, where this study was conducted, 13% of the samples taken from small-watershed sites exceeded the EPA's maximum contaminant level, indicating a potential health risk to nearby residents with shallow wells (9).…”
mentioning
confidence: 99%
“…Nos trabalhos feitos por Nolan et al (2002) e Squillace et al (2002), a degradação da qualidade da água subterrânea foi classificada e avaliada utilizando-se um círculo com raio de 500 m, centrado no poço. Em outros estudos, o uso da terra foi estudado dentro de raios variando de 100 a 3.200 m BRUCE;McMAHON, 1996;TROJAN et al, 2003).…”
Section: Methodsunclassified
“…Deste modo, os métodos de análise multivariada de dados têm sido cada vez mais utilizados em estudos ambientais devido à sua fácil aplicação e por reduzirem o número de dados em subgrupos menores correlacionados entre si, além de identificarem as variáveis que são responsáveis pela dispersão das observações BRUCE & McMAHON, 1996;NOLAN et al, 2002;SQUILLACE et al, 2002;TROJAN et al, 2003). Embora a utilização de um raio de influência arbitrário possa parecer simplista por não levar em conta as variáveis hidrodinâmicas do aquífero, considera-se possível sua utilização em …”
Section: Methodsunclassified
“…Nitrate is a highly soluble nutrient [12]. When nitrogen is applied to soil as a fertilizer or in manure, NO3 is often leached to below the root zone without reaching the target crop [1].…”
Section: Agricultural Water Nitrogen Use and Groundwater Nitrate Immentioning
confidence: 99%
“…In a comprehensive survey of domestic wells and wells of rural public water supply systems, Lockhart et al [16] showed that citrus, fruit and nuts, forage crops (often receiving dairy manure), and proximity to dairies were associated with the highest nitrate concentrations, while vineyards were among the agricultural land uses associated with the least nitrate concentration in domestic wells. Few data exist on N leaching rates from alfalfa, but observed groundwater concentration in regions with alfalfa as dominant crop (without corn rotation) are typically low in nitrate concentration [62,63]. Environmental crop modeling systems including nitrogen hazard indices [64,65], indicate that perennial crops and low or no N-input crops play a prominent role in protecting groundwater quality [1,66].…”
Section: Beneficial Agricultural Management Practices In Buffer Zonesmentioning
confidence: 99%